The Meaning of Cross-Cultural Communication Experience of International Students on Pesantren-Based Campuses - Setiawan, Erik; Chatamallah, Maman; Wiksana, Wiki Angga (Program Studi Ilmu Komunikasi, 2024)
This paper aims to examine the cross-cultural experiences of international students at Darussalam Gontor University in Indonesia. The study focuses on the interrelated themes of identity, language, and communication, and seeks to gain insight into how students from a range of countries, including Sudan, Chad, Turkey, and Thailand, experience life at this boarding university. A qualitative, phenomenological approach was employed by researchers, who conducted in-depth interviews and observations to gain insight into the experiences of these students. The findings indicate that identity is shaped by a process of comparison with others, driven by a desire to understand one's group. Language, particularly Arabic and English, plays a pivotal role, in supporting academic and social activities. However, students also engage in voluntary learning of Indonesian to enhance their interactions with the local population. Communication was identified as a crucial aspect of self-concept, self-actualization, happiness, and stress relief.